Long-term maintenance of a Deltacoronavirus infecting multiple bird species in Antarctica - Fernanda Gomes; Alexandre Freitas da Silva; Tatiana Prado; Paola Cristina Resende; Leonardo Corrêa Da Silva Junior; Wim Degrave; Maithê Magalhães; Adriana Vivioni; Yago José Mariz Dias; Marilda Siqueira; Martha Brandão; Luciana R. Appolinario; et al. (Microbiology Spectrum)
ABSTRACT Antarctica’s pristine environment and wildlife are of immense biological value, but the spread of viruses poses a substantial threat to the region’s fragile ecosystems. To investigate the presence of viruses in the region, we sampled the feces of different wild migratory birds at various localities in the South Shetland Islands and screened them for coronaviruses (CoVs) and avian influenza viruses (AIVs). Viral screening was performed by the conventional pancoronavirus RT-PCR protocol (CoVs), by one-step real-time RT-PCR (AIVs) followed by metatranscriptomic sequencing of positive samples. During January and February of 2023, we collected and examined 243 fecal samples representing skuas (Stercorarius spp.), kelp gulls (Larus dominicanus), Antarctic shags (Phalacrocorax bransfieldensis), Adélie penguins (Pygoscelis adeliae), chinstrap penguins (Pygoscelis antarcticus), gentoo penguins (Pygoscelis papua), and penguins of the Pygoscelis genus. All tested samples were negative for AIVs, and one sample from the colony of L. dominicanus tested positive for CoVs. Metatranscriptomic sequencing recovered a full Deltacoronavirus genome. Nucleotide and amino acid distance analysis revealed an unratified species of the genus Deltacoronavirus belonging to the subgenus Buldecovirus and to a previously proposed novel wild bird Deltacoronavirus clade previously identified in 2014 in P. papua penguin. The detection of the same virus infecting multiple bird species in Antarctica suggests a potential cross-species transmission or that this virus has a broad host range naturally infecting multiple bird species. The presence of CoVs in Antarctic migratory seabirds does not necessarily indicate a concern, as many of these viruses may have co-evolved with their hosts and circulate without causing clinical disease. However, continued monitoring of the Antarctic bird fauna, particularly focused on diseased animals and their association with this virus, warrants further investigations. This new finding brings valuable insights into virus dynamics among seabird populations, laying the groundwork for future investigations in this field and warning for the importance of viral surveillance on the Antarctic fauna.IMPORTANCEAntarctica’s ecosystems are highly vulnerable to external threats, and the spread of viruses could significantly impact the region’s wildlife. This study emphasizes the importance of monitoring migratory seabirds, as they can serve as vectors for viral transmission and eventually disease, including coronaviruses and avian influenza viruses. By detecting Deltacoronavirus in kelp gull feces, which was previously detected in a penguin, this research highlights the potential for cross-species transmission or multi-host infection capacity for this virus. These findings stress the need for increased viral surveillance in the Antarctic region, which could help protect local wildlife and provide essential data for understanding viral dynamics and infection in natural settings. Proactive monitoring will be crucial for mitigating the risk of zoonotic outbreaks and maintaining the integrity of Antarctica’s fragile ecosystems.